COMPLEX STRUCTURE LIFE CALCULATION PLATFORM BASED ON SECONDARY DEVELOPMENT OF ABAQUS - JIANG RenJie; YANG XiaoGuang; SHI DuoQi; DONG ChengLi; GUO GuangPing (Jixie qiangdu)
The critieal distance theory is suitable for caleulating the creep-fatigue life of complex structures, but the calculation efficiency of this method is very low in engineering. To overcome this shortcoming, Python language was used for the secondary development of Abaqus software. The developed software can calculate the creep-fatigue life of the structure by using the critical distance method. To improve analytical efficiency, various functions were developed in the software, including model information extraction, material parameter import and calculation result output, ete. The applicability of the software was verified by analyzing a high-pressure turbine blade. The results show that the software can efficiently calculate the creep-fatigue life of complex structures by simplifying the steps of the critical distance method, and it has certain engineering value.